Examining How Students with Visual Impairments Navigate Accessible Documents. (September 2020) - Singleton, Korey J.; Neuber, Kristine S.
Introduction: This exploratory study examined how students with visual impairments navigate accessible Word and PDF documents. Methods: Using a combination of video observations and semi-structured interviews, data were collected on participants' expressed and observed interactions with accessible Word and PDF documents. Results: Using a technique called summative content analysis, four core themes emerged from the findings: useful navigation elements or features (expressed and observed), strategies for navigating accessible documents, barriers to access, and coping strategies. Discussion: The findings suggest practical strategies for training participants to navigate accessible documents. Additionally, they identify the structural elements (i.e., headings, alternative text, etc.) most useful to the study's participants when navigating accessible documents. Implications for practitioners: As suggested by the findings of this study, universities should implement targeted training initiatives for faculty on basic document accessibility, which could include clearly defining the accessibility features included in a document. Likewise, targeted assistive technology training for students with visual impairments on how to access these elements could increase reading efficiency and reduce cognitive load.